The effect of learning media development on improving student motivation in islamic elementary schools - Ahmad Winarno; Anna Fadilatul Mahmudah; Nasilah Nasilah (EDUCARE: Journal of Primary Education Published by Faculty of Tarbiyah and Teacher Training, Kiai Haji Achmad Siddiq State Islamic University of Jember, East Java, Indonesia, 2025)
Learning in Islamic elementary schools is often characterized by teacher-centered instruction and limited use of interactive learning media, resulting in low student motivation and passive learning behaviors. The lack of engaging, technology-integrated media hinders students’ active participation, reduces learning interest, and limits the development of meaningful and motivating learning experiences. This study investigates how learning media development is designed, validated, and implemented to effectively enhance student motivation in Islamic elementary schools through feasible and engaging instructional media. This study used a research and development approach with the ADDIE model involving 25 fifth-grade students. Data were collected through observations, interviews, questionnaires, and pretest–posttest, and analyzed using Likert scales and N-Gain to assess feasibility and effectiveness. The study concludes that ADDIE-based Digital Crossword effectively enhances elementary students’ motivation, engagement, and conceptual understanding in Natural and Social Sciences. Acting as a pedagogical mediator, the media combines multimodal elements, game mechanics, and immediate feedback to foster active, meaningful learning. High expert validation and positive student responses confirm its feasibility and pedagogical potential, with moderate N-Gain improvement observed. This study is significant as it provides empirical evidence that ADDIE-based Digital Crossword media effectively enhances student motivation, engagement, and conceptual understanding, offering a practical, scalable model for interactive, game-based learning in elementary education.